SERTIFIKASI GURU: ANTARA PROFESIONALISME, HARAPAN DAN TANTANGAN - Suyadi, Suyadi (LP3M STAI DARUSSALAM LAMPUNG, 2012)
The teacher certification is an official program to improve teacherâs quality as well as his/her social status. There are two ways of certification of teacher in working, namely by portfolio assessment and by professional education assessment. But the certification actually runs on seniority, not professionally. It results that many certified teachers will be soon retired. The fact shows that the certified teachers are not always professional ones and in turn does not always improve the educational quality. Therefore the certification should be professionally practiced so the certified teachers verily improve the educational quality.Â Key words: sertifikasi guru, sertifikasi profesional, mutu pendidikan.